2023
DOI: 10.1002/ajcp.12678
|View full text |Cite
|
Sign up to set email alerts
|

Identifying abolitionist alignments in community psychology: A path toward transformation

Abstract: Psychology is grounded in the ethical principles of beneficence and nonmaleficence, that is, “do no harm.” Yet many have argued that psychology as a field is attached to carceral systems and ideologies that uphold the prison industrial complex (PIC), including the field of community psychology (CP). There have been recent calls in other areas of psychology to transform the discipline into an abolitionist social science, but this discourse is nascent in CP. This paper uses the semantic device of “algorithms” (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…There is the potential to divert people from incarceration (Epperson et al, 2021). For instance, DaViera et al (2023) suggested that psychologists engage in more emancipatory science. We encourage research to shift their focus to evidence-based solutions to criminal legal system transformation or abolishment.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is the potential to divert people from incarceration (Epperson et al, 2021). For instance, DaViera et al (2023) suggested that psychologists engage in more emancipatory science. We encourage research to shift their focus to evidence-based solutions to criminal legal system transformation or abolishment.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Abolition from the prison industrial complex (PIC) is “focused on eliminating punitive measures, practices, policies and policies that control, surveil, and harm people” (Paine et al, 2021, p. 10). DaViera et al (2023) note that “one cannot reform the PIC and, thus, should not collaborate with its stakeholders” (p. 8). This would include not aligning with carceral systems (i.e., law enforcement, corrections).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation